Exploring climate change adaptation pathways for the agricultural sector in Arba Minch Zuria and Bonke districts: Based on CCAFS climate analogue tool - Israel Gebresilasie Kimo; Tewodros Addisu Yate; Bisrat Elias Cholo; Thomas Torora Minda; Esatu Bekele Bayde (Climate Services)
Ethiopia relies heavily on rain-fed agriculture, making its agricultural sector highly vulnerable to climate variability and change. Adaptation strategies informed by projections of future climate conditions can help mitigate these impacts effectively. This study demonstrates how a science-based approach, specifically the climate analogues methodology, can be used to envision site-specific future agricultural conditions and identify potential adaptation strategies. While such approaches have been increasingly applied elsewhere, their use in Ethiopia remains limited. Therefore, this study applies the analogues tool developed by the Climate Change, Agriculture and Food Security (CCAFS) program to identify a site whose current climate is analogues to the future climate of the study areas—Arba Minch Zuria and Bonke Districts, aiming to highlight potential adaptation pathways. The result shows that Key-Afer and Boreda in Ethiopia, as well as Migori and Narok counties in Kenya, are analogue sites to Arba Minch Zuria. Furthermore, Dita Zada and Chencha in Ethiopia are analogue sites to Bonke. Farmers in Key-Afer analogue site engage in various climate response strategies, including planting different crop varieties (90.7 %), changing planting dates (51.8 %), and soil and water conservation measures (46.3 %). Moreover, farmers in Migori County, Kenya, analogue site apply mixed farming (96.5 %), non-intensive dairying (95.1 %), and establish their own feed (92.4 %). Understanding current climatic conditions and agricultural practices in these analogue areas can inform adaptation planning, as they provide a glimpse into the future conditions of the study area. The findings of this research offer valuable insights for policymakers and the scientific community aiming to design effective climate change adaptation strategies.